Are Multi‐Decadal Fluctuations in Arctic and Antarctic Surface Temperatures a Forced Response to Anthropogenic Emissions or Part of Internal Climate Variability? - Mark R. England (Geophysical Research Letters)
Abstract In this study, we investigate the drivers of observed multi‐decadal fluctuations in Arctic and Antarctic surface temperatures using multiple large ensembles of climate simulations and single‐forcing ensembles. We find that the observed oscillation in Arctic surface temperature around a linear trend since 1920 is a forced response to emissions of anthropogenic aerosols and greenhouse gases. In contrast, we show that observed multi‐decadal Antarctic surface temperature fluctuations are partially related to Pacific decadal variability which influences the climate of West Antarctica. Lastly, we demonstrate that internally driven multi‐decadal fluctuations at the two poles are not systematically correlated in any climate model examined here, as had been previously suggested. We conclude by discussing the implications of these results for understanding projections of Arctic and Antarctic surface climate of the coming decades.